1996
DOI: 10.1111/j.1365-2648.1996.tb01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of nurses in a general hospital towards people with learning disabilities: influences of contact, and graduate‐non‐graduate status, a comparative study

Abstract: A review of the literature suggests people with learning disabilities are viewed negatively by others in society. Such negative views have also been found among many health care professionals, including nurses. This study measured the attitudes of a randomly selected sample of nurses in a general hospital (n = 31) towards people with learning disabilities. The study involved a triangulation approach utilizing a Likert scale attitude measurement questionnaire. Two comparisons between subjects in the study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
4
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 19 publications
3
57
4
2
Order By: Relevance
“…No relationships were found between years of experience of teaching children with a learning disability or currently having a child with a learning disability in the classroom and attitude scores. This is at odds with research which has indicated that previous experience of or contact with people with a learning disability can improve attitudes (Slevin & Sines, 1996).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…No relationships were found between years of experience of teaching children with a learning disability or currently having a child with a learning disability in the classroom and attitude scores. This is at odds with research which has indicated that previous experience of or contact with people with a learning disability can improve attitudes (Slevin & Sines, 1996).…”
Section: Discussioncontrasting
confidence: 51%
“…Research in both the health and education sector has indicated that previous experience of or contact with people with a learning disability can improve knowledge (Johnson & Cartwright, 1991), reported knowledge (Golder et al, 2005) and attitudes (Slevin & Sines, 1996).…”
Section: Attitudes and Children With A Learning Disabilitymentioning
confidence: 99%
“…Navedeno potvrđuju Slevin i Sines u istraživanju stavova medicinskih sestara prema osobama s invaliditetom. Oni naglašavaju da češći kontakt medicinskih sestara s tim osobama rezultira pozitivnijim stavovima prema njima, ali i da medicinske sestre s većim stupnjem obrazovanja imaju veći stupanj razumijevanja [8].…”
Section: Rasprava/discussionunclassified
“…In particular, a study comparing the attitudes of physicians to those of parents of children with cognitive impairments found that physicians under-estimated parents' beliefs about their families' quality of life and about the place of people with cognitive impairments in society [4]. Another study documented that nurses, compared with the general population, had more negative attitudes towards people with cognitive impairments [5]. Finally, as the practice of medicine becomes increasingly business-like, a study of business-school students' views regarding employment of people with disabilities revealed disadvantageous biases [6].…”
Section: Introductionmentioning
confidence: 97%